PREVENTION OF ALLERGIES IN CHILDREN - E. A. Vishneva; L. S. Namazova-Baranova (Педиатрическая фармакология)
The article is dedicated to the issue of preventing allergies in children. Increase in the spread of allergic diseases among children and adolescents remains one of the most significant medical and social issues and constitutes a heavy burden for healthcare budgets of many countries around the world. The Federal clinical recommendations must become modern guidelines for practicing clinicians everywhere; these are modern regulatory documents – protocols of medical care rendering to children with various allergic manifestations. The authors substantiate complex approach to the therapy of allergic diseases and determine the role of preventive measures and elimination of trigger effects. The authors traditionally distinguish between primary, secondary and tertiary measures and demonstrate their orientation. They consider the issue of preventing respiratory infections, which often constitute a factor of exacerbation of chronic allergic processes and are one of the frequent causative agents of allergic inflammation. The optimal preventive effect and maximum reduction in the incidence rate of respiratory infections may be achieved by combining vaccination and immune pharmacotherapy.